Seroepidemiology of Toxoplasmosis among People Having Close Contact with Animals - Brandon-Mong, Guo-Jie; Che Mat Seri, Nurul Asma Anati; Sharma, Reuben Sunil-Kumar; Andiappan, Hemah; Tan, Tian-Chye; Lim, Yvonne Ai-Lian; Nissapatorn, Veeranoot (Frontiers in Immunology, 2015)
A cross-sectional study was conducted to determine the seroepidemiology of Toxoplasma gondii infection among individuals who have close contact with animals. The association between plausible risk factors and the seropositivity for Toxoplasma was examined. A total of 312 blood samples were collected form veterinarians(38), veterinary technicians(45), veterinary students(194) and pet owners(35) from several veterinary hospitals and clinics in the area of Klang Valley, Malaysia. About 4cc of blood samples drawn from agreed participants were processed for measurement of anti-Toxoplasma IgG and IgM antibodies as well as avidity test of Toxoplasma IgG by ELISA.Meanwhile, the demographic profiles and possible risk factors of these participants were also recorded in the standardized data collection sheets.Overall seroprevalence of toxoplasmosis was observed in 62 (19.9%)participants where 7(18.4%) veterinarians, 15(33.3%)veterinary technicians, 29(14.9%)veterinary students and 11(31.4%) pet owners were infected. Out of 19.9% positive samples for toxoplasmosis, 18.3% of these samples were positive for IgG antibody, 1.0% was positive for IgM antibody and 0.6% were positive for both IgG and IgM antibodies.Positive samples for IgM antibody and for both IgG and IgM antibodies were further analysed by IgG avidity test. Out of 5 samples tested for avidity test, 4 samples showed a high avidity results which means infection occurred in the past whereas only 1 sample showed a recently acquired infection. Univariate analysis showed that age group, gender,study population, gardening, task performance and working duration were significantly associated with seropositivity of toxoplasmosis. Further analysis by multivariate analysis using logistic regression showed that age group more than or equal to 30 years old (OR=0.34, 95% CI=0.18-0.63, p=0.001)and working or study duration more than 10 years in handling with animals(OR=5.07, 95% CI=1.80-14.24, p=0.002)were identified as significant